Meta-Analysis: Effects of Unsafe Action and Work Experience on Occupational Exposure to Needlestick Injury among Health Workers in the Hospital - Andriani, Nurul Dwi; Sumardiyono, Sumardiyono; Murti, Bhisma (Journal of Health Policy and Management, 2022)
Background: Needlestick injury is a dangerous work accident that causes blood contact with pa-tients and is at risk of being infected with blood borne diseases such as hepatitis B virus (HBV), hepatitis C (HCV), and human immunodeficiency virus (HIV). The purpose of this study was to analyze the influence of unsafe behavior factors on the incidence of accidents due to needlestick injury to health workers in hospitals. Subjects and Method: This research was conducted using a systematic review and meta-analysis study design using PICO, population: health workers, intervention: unsafe action and lack of work experience. Comparison: safe action and good work experience, Outcome: Needlestick Injury (NSI) incident. The articles used in this study came from 4 databases, namely Pubmed, ScienceDirect, ProQuest and Google scholar. The keywords of the article are ("Needle Stick Injury" or "Sharp Injury") AND aOR. The articles included in this study are full paper articles, observational study designs, 2011-2021 and the size of the relationship between Adj Odds Ratio Results: A total of 19 observational studies (case-control and cross-sectional) with 28,487 health workers from the African Continent (Egypt and Ethiopia), the Asian Continent (Thailand, Taiwan, Malaysia and Indonesia) and the European Continent (Bosnia and Herzegovina) were analyzed. From data processing, it was found that unsafe action increased the incidence of Needlestick Injury (NSI) in health workers in hospitals by 2.79 times higher than health workers who behaved safely (safe action) and statistically significant (aOR= 2.79; 95% CI= 2.18 to 3.67; p<0.001). Work Experience increases the incidence of Needlestick Injury (NSI) in health workers in hospitals by 1.97 times higher than health workers who have good work experience and is statistically significant (aOR= 1.97; 95% CI= 1.16 to 3.34; p = 0.010) . Conclusion: The influence of human factors, especially unsafe action, in increasing the incidence of needlestick injuries in health workers.Keywords: needlestick injury, sharp injury, unsafe actionCorrespondence:Nurul Dwi Andriani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: nurul.d.andriani@gmail.com. Mobile: +6282137279586.Journal of Health Policy and Management, 07(01): 58-71https://doi.org/10.26911/thejhpm.2022.07.01.06.